Accessibility of assistive technologies among primary school learners with visual impairments in Tanzania - John, Bahati Karusha; Stackus, Okwaput (S&Co Publishing, 2025)
This study examined the accessibility of Assistive Technologies (ATs) for Learners with Visual Impairments (LwVI) in primary schools in Tanzania. The primary aim was to scrutinize the availability of both high-tech and low-tech ATs, as well as the enabling infrastructure used to enhance the use of ATs in teaching and learning for LwVI. This study employed an exploratory case design within a qualitative approach, in which data were collected through observations and semi-structured interviews and analyzed using thematic data analysis procedures. Data was gathered from five teachers, the Deputy Head Teacher, five LwVI from one primary school, and the District Special Needs Education Officer in the district where the school is located. The study revealed that despite government efforts to promote equitable quality education within an inclusive framework, LwVI in primary schools remain marginalized due to the inadequacy of both low-tech and high-tech ATs, as well as insufficient enabling infrastructure necessary to support their use. This finding is inconsistent with the modern world's emphasis on digitizing education, particularly in ensuring equitable quality education for persons with disabilities. Therefore, a comprehensive approach is needed, including earmarking resources for AT procurement, fostering robust partnerships among stakeholders—including the government and non-governmental organizations—for the acquisition and maintenance of ATs, and upgrading the enabling infrastructure to support their sustainable use. Additionally, there is a need to develop a comprehensive framework for evaluating AT availability and a database for tracking the resources available in schools. These two components should inform policymaking practices and stakeholder decisions.